Pengaruh Reword Dan Punishment Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Polres Tanah Datar - Shaqinah Fadliatika; M. Afuan; Deni Saputra (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of reward and punishment on employee performance through work discipline as an intervening variable at Polres Tanah Datar. In the era of globalization, characterized by increasing competition and demands for professional work standards, organizations are required to optimize human resource management to achieve organizational goals effectively. Reward and punishment represent management strategies used to improve employee discipline and performance. This research employs a quantitative approach using a survey method through questionnaires as the data collection instrument. The research population consists of all employees at Polres Tanah Datar, with a sample of 53 respondents determined using a saturated sampling technique. Data analysis was conducted using the SmartPLS method to examine both direct and indirect relationships among variables. The results indicate that reward and punishment do not have a significant direct effect on employee performance. However, reward and punishment have an indirect effect on performance through work discipline as an intervening variable. These findings suggest that improving employee performance is more effectively achieved through strengthening work discipline as a mediating mechanism in the implementation of reward and punishment systems within the organizational environment.